2006
DOI: 10.1186/cc4428
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objective To examine the effects of short-term cyclic stretch on apoptosis in alveolar type II cells (A549). To study in vitro the direct influence of alveolar type II cells on mechanical stretch. Methods A549 were treated with different doses of lipopolysaccharide (LPS), 0 ng/ml, 1 ng/ml, 10 ng/ml, 100 ng/ml, 1000 ng/ml, and then A549 were lengthened 5%, 15%, 30% using a FLEXCELL tension unit 4000, a vacuum-driven device that applies strain to cells, which were cultured in six-well plates coated with collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A retrospective study in the United Kingdom identified a high-risk population of 12.5% regarding all surgical procedures, which accounted for 83.8% of overall mortality and represented a prolonged hospital stay (22). To optimize perioperative the hemodynamic status of this high-risk population, the most frequent parameters that have been used next to standard parameters are cardiac output (CO) and/or oxygen delivery (DO 2 ).…”
Section: Hypovolemia and Outcomementioning
confidence: 99%
“…A retrospective study in the United Kingdom identified a high-risk population of 12.5% regarding all surgical procedures, which accounted for 83.8% of overall mortality and represented a prolonged hospital stay (22). To optimize perioperative the hemodynamic status of this high-risk population, the most frequent parameters that have been used next to standard parameters are cardiac output (CO) and/or oxygen delivery (DO 2 ).…”
Section: Hypovolemia and Outcomementioning
confidence: 99%